The Study of Corrective Written Feedbacks in Stu dents’ Written Works in Al Falah Junior High School Sidoarjo Annisa’ Karimatul Fikroh - Fikroh, Annisa' Karimatul (RETAIN, 2021)
In writing, feedback can be defined as input from a teacher to the students with the effect of providing information to the students for revision. Many studies have been conducted on the effect of the type of feedback on learners’ writing. Many of them reported that there is significant improvement in students’ composition made by the students who are given indirect corrective written feedback. There is one research that observed the implementation of indirect corrective written feedback by professional English teacher in in a private junior high school in Sidoarjo. However, the research does not observe another teacher in the school that may give the same or different kinds of feedback. Furthermore, in teaching and learning process of writing there must be more than one feedback given by the teacher. Hence, this research wants to find out kinds of feedback the teacher gave and the reason for giving it. Furthermore, it will observe the result of students’ written products. Kata Kunci: indirect corrective feedback, direct feedback, written feedback, writing products.